Circular RNA and Its Roles in the Occurrence, Development, Diagnosis of Cancer - Zhang, Yue; Zhang, Xinyi; Xu, Yumeng; Fang, Shikun; Ji, Ying; Lu, Ling; Xu, Wenrong; Qian, Hui; Liang, Zhao Feng (Frontiers in Oncology, 2022)
Circular RNAs (circRNAs) are a type of non-coding single-stranded covalently closed circular RNA, which are mainly produced by reverse splicing of exons of precursor mRNAs (pre-mRNAs). The characteristics of high abundance, strong specificity, and good stability of circRNAs have been discovered. A large number of studies have reported its various functions and mechanisms in biological events, such as the occurrence and development of cancer. In this review, we focus on the classification, characterization, biogenesis, functions of circRNAs, and the latest advances in cancer research. The development of circRNAs as biomarkers in cancer diagnosis and treatment also provides new ideas for studying circRNAs research.